Degradação ruminal de dietas à base de milho em substituição ao grão de sorgo com alto tanino - Almeida, Gabriel Henrique Oliveira (2015)
This study aimed to evaluate the effects of replacing corn with sorghum grain with high tannin on the intake, digestibility, ruminal parameters (pH, N-NH3 and VFA) degradability of the dry matter of sorghum grain with high tannin and counting of ciliated protozoa in the rumen cannulated cattle. We used four adult cattle castrated male crossbred Holstein x Zebu with a live weight of 518.8 ± 30.6 kg, distributed in a Latin square design (DQL) following 4x4 model. The treatments consisted in the replacement of corn by sorghum grain with high tannin in increasing levels of 0, 33, 67 and 100% of dry matter (% MS) and as a source of roughage, silage of elephant grass. All analyzes were performed using the statistical package (SAS Institute Inc. 2009, Cary, NC). There was no significant effect on DM intake and nutrient (P> 0.05) on the basis of corn replacement levels for sorghum. There was a decreasing linear effect (P <0.05) on the digestibility of CP and only NDFap the measure that increased the proportion of sorghum in dietas. As measurements of ruminal parameters were performed before, 2, 4 and 6 hours after suplementação.O rumen pH ranged between 6.1 and 6.7 during the collection times, with no significant difference between treatments (P = 0.57) or for treatment x time interaction (P = 0.24) But the collection schedule showed a quadratic effect (P <0.05), reaching the lowest values four hours after delivery of the feed. The N-NH 3 values ranged between 3.18 and 20.97 mg / dL during the collection times, no significant differences between treatments (P = 0.35), or interaction treatment x time (P = 0, 66), however, showed a quadratic effect in relation to collection time (P <0.05), with peak production two hours after delivery of the feed. The concentrations of AGVs (acetic, propionic and butyric) and the acetate / propionate ratio did not differ between treatments (P> 0.05), nor was no interaction between treatment x time (P> 0.05) for these variables, however , acetic and propionic acid showed increasing linear effect (P <0.05) for the collection times to replace corn by sorghum. The ciliate protozoa count decreased linearly (P <0.05) when raising the level of sorghum in the diets. The ground corn can be replaced by grain sorghum with high tannin diets to adult cattle.